Analysis of Morphological Features of Sargalu Region in Sulaymaniyah Governorate, North of Iraq, by using Geographic Information System - Hussain, Ali Abdul-Jaleel; Rasheed, Muaid Jassim (Iraqi Journal of Science, 2021)
It is an ideal area of research to examine related indicators to anticipate relative tectonic activities, where there is a broad range of geological formations with elements of different sedimentary rocks. This study includes assessing and evaluating the relative tectonic activities within the Sargalu area by using a morphometric approach, which involved the use of different indices that can explain and help understanding the geometry, development level, lithology, and structural disturbance on a sub-basinal level. The research was accomplished by using ArcGIS 10.5 hydrology tools to design the drainage system of each studied stream. The Advanced Spaceborne Thermal Emission Radiometer (ASTER) satellite imagery data and the Digital Elevation Model (DEM 90m) were used. Moreover, Global Mapper and Statistical Package for the Social Sciences (SPSS) were applied. DEM datasets of ASTER were used for watershed delineation. Also, 14 sub-basins were delineated in the Sargalu area. Morphometric indices used include Shape Related Indices, such as Rc, Bs, Rf, Ls, Re, T, and Af. Basin asymmetry factor (Af) and several geomorphic indices were also utilized. Based on the shape related indices (Rc, Rf, Re, Ls, and Cc), the results were found to be similar and, for most sub-basins, had an elongated nature. The elongated basins are connected with tectonically active areas, while the circulated basins are connected with the tectonically undisturbed environment.